Transportation network companies and taxis - Leisy, Craig A., author.
1 online resource.
Keywords: Transportation Network Companies and Taxis: The Case of Seattle is a modern economic case history and thorough analysis of the devastating impact of the transportation network company (TNC) industry (Uber and Lyft) on the taxicab industry in Seattle, Washington, beginning in 2014. The events that transpired and lessons learned are applicable to most large cities in North America, Europe and Australia. As the regulator of the taxicab and TNC industries in Seattle during this period, the author offers a unique insider perspective. The book also provides internal operating statistics on the TNC industry, which are available here for the first time. Despite the spectacular growth of the TNC industry, growth rates have steadily declined and may fall to zero by 2019 or 2020, while the taxicab industry appears to have begun a modest recovery. This book offers a thorough explanation of how and why this decline has happened. It explains the taxicab industry, economic deregulation, competitive market failure, market disruption, price elasticity of demand and other concepts. There is also a wealth of data, computations and analysis for the specialized reader. This book considers the past, present and future of the taxicab and TNC industries in Seattle, It is recommended for both the general reader and industry professionals.